225 INTRAUTERINE PROGRAMMING OF OFFSPRING OBESITY: THE ROLE OF MATERNAL DIABETES. (1st January 2005) - Lee, T.; Huang, J.; Chen, B.; Lu, M.
Abstract : Obesity prevails as an increasingly widespread metabolic disorder of energy intake and balance with multifactorial causes involving both genetics and environmental influences. The prenatal period has been highlighted as a sensitive and critical stage in the development of obesity and has been a focus of basic and clinical research efforts for prevention. The modification of substrate transfer to the fetus may subsequently alter organ development and function involved in energy metabolism. Although there is no single mechanism for fetal programming of obesity in the intrauterine environment, the strongest evidence is for the role of maternal diabetes. The purpose of this study was to investigate the possible pathophysiologic mechanisms leading from intrauterine exposure to diabetes mellitus to adolescent offspring obesity later in life. A second purpose was to evaluate the epidemiologic evidence that links maternal diabetes mellitus to offspring obesity. Epidemiologic data was collected in a systematic review of the literature using PubMed and MDconsult. Six studies were identified that met the inclusion and exclusion criteria The evidence suggests that aside from genetic factors, the altered intrauterine environment in maternal diabetes may predispose offspring to adolescent obesity and glucose intolerance. Proposed mechanisms suggest that a fetus exposed to hyperglycemic conditions can be programmed to develop a dysregulated adipoinsular feedback pathway leading to adolescent obesity. Therefore, careful monitoring of maternal glucose levels during pregnancy may have a significant impact on the prevention of adolescent obesity.